Evaluating the Implementation of the Materiality Concept in Sustainability Reports: A Case Study of LLDikti III Regional Universities - Wiliam, Andi; Darmo, Ika Suhartanti; Angelica, Patricia (Journal of Loomingulisus ja Innovatsioon, 2025)
In sustainability reports, there is a debate between two materiality concepts, namely the GRI concept & the SASB concept. Most companies that present Sustainability Reports prioritize two materiality concepts: the GRI and the SASB. Discuss sustainability reports that financially and non-financially impact University operations using the GRI and SASB materiality concepts in their application. The research was conducted to find the application of materiality in sustainability reports, which is dominant in universities in the LLDikti III region. This qualitative research uses surveys and interviews with professional teaching staff at several universities in the LLDikti III region, including Multimedia Nusantara University, Binus University, and Tarumanegara University. This research examines the application of sustainability reports, including the differences in the materiality concept applied between GRI and SASB, as well as the perceived impact and reasons related to the choice of the materiality concept applied. Based on the results of discussions in research regarding the materiality concept in sustainability reports, it was found that three universities were selected in the Kopertis region. III is more inclined towards the application of the GRI materiality concept. This research suggests implementing GRI or SASB materiality because they are considered more effective, improve quality and performance, and facilitate careful planning.